Platelet formation and activation are influenced by neuronal guidance proteins - Tang, Linyan; Liu, Chao; Rosenberger, Peter (Frontiers in Immunology, 2023)
Platelets are anucleate blood cells derived from megakaryocytes. They link the fundamental functions of hemostasis, inflammation and host defense. They undergo intracellular calcium flux, negatively charged phospholipid translocation, granule release and shape change to adhere to collagen, fibrin and each other, forming aggregates, which are key to several of their functions. In all these dynamic processes, the cytoskeleton plays a crucial role. Neuronal guidance proteins (NGPs) form attractive and repulsive signals to drive neuronal axon navigation and thus refine neuronal circuits. By binding to their target receptors, NGPs rearrange the cytoskeleton to mediate neuron motility. In recent decades, evidence has indicated that NGPs perform important immunomodulatory functions and influence platelet function. In this review, we highlight the roles of NGPs in platelet formation and activation.